Examining marginal sequence similarities between bacterial type III secretion system components and Trypanosoma cruzi surface proteins: horizontal gene transfer or convergent evolution? - Silva, Danielle C.; Silva, Richard C.; Ferreira, Renata C.; Briones, Marcelo R. (Frontiers in Genetics, 2013)
The cell invasion mechanism of Trypanosoma cruzi has similarities with some intracellular bacterial taxa especially regarding calcium mobilization. This mechanism is not observed in other trypanosomatids, suggesting that the molecules involved in this type of cell invasion were a product of (1) acquisition by horizontal gene transfer; (2) secondary loss in the other trypanosomatid lineages of the mechanism inherited since the bifurcation Bacteria-Neomura (1.9 billion to 900 million years ago) or (3) de novo evolution from non-homologous proteins via convergent evolution. Similar to T. cruzi, several bacterial genera require increased host cell cytosolic calcium for intracellular invasion. Among intracellular bacteria, the mechanism of host cell invasion of genus Salmonella is the most similar to T. cruzi. The invasion of Salmonella occurs by contact with the host's cell surface and is mediated by the type III secretion system (T3SS) that promotes the contact-dependent translocation of effector proteins directly into host's cell cytoplasm. Here we provide evidence of distant sequence similarities and structurally conserved domains between T. cruzi and Salmonella spp T3SS proteins. Exhaustive database searches were directed to a wide range of intracellular bacteria and trypanosomatids, exploring sequence patterns for comparison of structural similarities and Bayesian phylogenies. Based on our data we hypothesize that T. cruzi acquired genes for calcium mobilization mediated invasion by ancient horizontal gene transfer from ancestral Salmonella lineages.